IDENTIFYING STUDENT'S CRITICAL RESPONSES TO LITERARY WORK IN LITERATURE CLASS - Slamet Riyadi; Kristianto Setiawan; Ashari Ashari (LEAD (Language, Education and Development), 2021)
The aim of this research is to identify the responses resulted from the activity of critical reading to literary work using Critical Discourse analysis in Introduction to Literature class in the English Education Study Program, Faculty of Culture UNSOED. The method used is qualitative method with a case study as the design. Data collection is carried out through interviews, and document studies so that the data obtained from these methods can be mutually reinforcing. Furthermore, 32 students of the Introduction to Literature course became the respondents in the study that was carried out for 8 months. The result of the study showed that there were three types of responses given by students namely - summary level 16%, -moral level 25%, -critical response level: 59%